Sex and ambivalence: LGBTQ youth negotiating sexual feelings, desires and attractions. Issue 3 (3rd July 2018) - Clarke, Kyra; Cover, Rob; Aggleton, Peter
ABSTRACT: In popular and academic discourse, sexual identity is regularly linked to a concept of sexual engagement with others. Recent thinking on sexuality has, however, opened up the possibility of understanding 'identity' in ways different from sexual behaviour. This paper considers data from the Australian Queer Generations project, in which findings indicate that young Australian participants express complex ambivalences towards sex and sexual expression, and disavowals of the importance of sex. We consider what this might mean for young people's gender and sexual identities as well as implications for support for LGBTQ young people.